Mental health help-seeking among individuals with breast cancer: A qualitative exploration of women’s and healthcare practitioners’ perspectives - Nurdiana Mohammad Hussin; Nik Ruzyanei Nik Jaafar; Idayu Badilla Idris; Azmawati Mohammed Nawi (PLoS ONE, 2026)
Individuals with breast cancer (BC) experience significant psychological distress, yet their utilization of mental health services remains low. This study identified key factors influencing help-seeking behavior through integrated Theory of Planned Behavior (TPB) and Health Belief Model (HBM) frameworks. We conducted in-depth interviews (IDIs) with eight BC patients and nominal group technique (NGT) with six health professionals, followed by Fuzzy Delphi Method (FDM) to assess expert consensus. The IDIs revealed that the individuals with BC recognized the value of professional psychological support but were reluctant to engage with these services personally. The participants identified emotional thresholds for help-seeking, expressed preference for informal support networks, and demonstrated varied understanding of mental health professional roles. The FDM evaluation demonstrated strong expert consensus across all assessed elements, particularly those related to emotional support mechanisms. Three barrier categories emerged: individual factors (mental health literacy, autonomy preferences), social factors (family support, cultural stigma), and systemic factors (healthcare integration gaps). Expert consensus exceeded 80% agreement across all domains.This study identified a complex interplay between individual psychological barriers and systemic factors affecting mental health help-seeking among individuals with BC. Effective interventions must address psychological barriers and healthcare delivery factors while respecting individual autonomy in coping choices. A multi-level approach targeting individual education, family support systems, and healthcare integration is recommended to improve mental health service utilization among individuals with BC.